Anode catalyst, electro-catalysis system containing anode catalyst and method for producing hydrogen through electro-catalysis ethylene glycol coupled seawater electrolysis

By using an anode catalyst supported by foam metal substrates with MCo2O4 and palladium nanoparticles in seawater electrolysis, the corrosion problem of chlorine elements on the catalyst in seawater electrolysis is solved, and low power consumption and high efficiency hydrogen production is achieved.

CN119571387APending Publication Date: 2025-03-07TECHNICAL INST OF PHYSICS & CHEMISTRY - CHINESE ACAD OF SCI
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202311153150.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-09-07
Publication Date
2025-03-07

AI Technical Summary

Technical Problem

In the existing seawater electrolysis hydrogen production technology, the adverse effects of chlorine on the catalyst lead to corrosion and high power consumption, making it difficult to achieve stable and efficient seawater electrolysis.

Method used

Using foam metal as the substrate material, anode catalyst supported by MCo2O4 spinel oxide and palladium nanoparticles was prepared by hydrothermal reaction and annealing treatment, combined with aqueous chloropalladium acid solution to improve the stability and performance of the catalyst.

Benefits of technology

It achieves low operating voltage (1.14V), high glycolic acid yield (92.6%) and high hydrogen recovery (99%) when reaching industrial-grade current density under seawater conditions, and maintains stable electrolytic performance for more than 100 hours.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119571387A_ABST
    Figure CN119571387A_ABST
Patent Text Reader

Abstract

The invention provides an anode catalyst, an electro-catalysis system containing the anode catalyst and a method for producing hydrogen through electro-catalysis ethylene glycol coupled seawater electrolysis. The anode catalyst includes a foam metal as a substrate material; the MCo2O4 spinel oxide is loaded on the foam metal; the palladium nano particles are loaded on the MCo2O4 spinel oxide; wherein M represents metal Mn, Fe, Ni, Cu or Zn. The anode catalyst is applied to hydrogen production through electrocatalysis of ethylene glycol coupled with seawater electrolysis, and shows relatively high selectivity, catalytic activity and stability, which are specifically embodied in that when the industrial-grade current density (600mA cm < 2 >) is reached, the working voltage is only 1.14 V; when the ethylene glycol is completely electrolyzed, the yield of the glycollic acid is as high as 92.6%; meanwhile, the anode catalyst can realize stable electrolysis for more than 100 hours under a seawater condition, and is superior to all current palladium-based ethylene glycol oxidation catalysts.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of electrochemical catalysis, and specifically comprises an anode catalyst, an electrocatalytic system comprising the anode catalyst, and a method for producing hydrogen by electrocatalytic ethylene glycol coupled with seawater electrolysis. Background Art

[0002] Green hydrogen has an excellent energy density (142MJ / Kg -1 ) and zero carbon emissions, is an important part of sustainable clean energy to achieve carbon neutrality. Using renewable energy such as solar and wind power to produce high-purity hydrogen through water electrolysis is an attractive strategy in the field of sustainable energy, but due to the unaffordable cost of electricity (> US$4 kg -1 H2), which only accounts for 4% of the world's total hydrogen production. In addition, water electrolysis requires a large amount of scarce pure water, which may hinder its application in arid, onshore and offshore areas. If the inexhaustible seawater (accounting for 96.5% of the world's water resources) is used, the problem of pure water consumption will be effectively solved.

[0003] The difficulty in using seawater for hydrogen electrolysis is the adverse effect of chlorine on the catalyst. - At the theoretical oxidation potential (1.72 V), the chlorine electrooxidation reaction (ClOR) will compete with the oxygen evolution reaction (OER) to produce toxic Cl2 (acidic) or corrosive ClO - (alkaline). One of the strategies to inhibit ClOR is to limit the overpotential of OER to below 0.48V, but such a small overpotential is not enough to meet the requirements of industrial standard current density. If a cation selective layer or a chloride-free electrolyte is introduced for electrolysis, the anode can have a higher resistance to chlorine corrosion at industrial-grade current density. However, chlorine crossover and corrosion, as well as the huge power consumption caused by high cell voltage requirements (>1.7-2.4V), are still difficult to eliminate problems in the long-term seawater electrolysis process. Therefore, it is imperative to develop a catalyst that can stably electrolyze seawater and has high catalytic performance.

[0004] Biomass derivative ethylene glycol (EG) is the simplest diol with low toxicity, low cost (US$350 / ton) and high hydrogen content. It has been widely studied in the field of biomass conversion into value-added chemicals. For example, glycolic acid (GA), the oxidation product of EG, has the highest value (US$6950 / ton) and has unique chemical properties, showing great potential in the synthesis of biodegradable materials. Therefore, it is a direction worth exploring in the field of electrochemical catalysis to establish an electrocatalytic system for EG-coupled seawater electrolysis to produce hydrogen, obtain high-value-added glycolic acid and achieve energy-saving hydrogen production. Summary of the invention

[0005] In view of the above problems existing in the prior art, the first object of the present invention is to provide an anode catalyst. The anode catalyst exhibits high selectivity, catalytic activity and stability in the electrocatalytic ethylene glycol coupled seawater electrolysis hydrogen production, not only obtaining high value-added glycolic acid, but also co-producing green hydrogen, and has high application value.

[0006] The second object of the present invention is to provide a method for preparing the anode catalyst as described above.

[0007] The third object of the present invention is to provide an application of the anode catalyst as described above in the electrocatalytic production of glycolic acid from ethylene glycol.

[0008] A fourth object of the present invention is to provide an electrocatalytic system for preparing glycolic acid from ethylene glycol.

[0009] A fifth object of the present invention is to provide a method for producing hydrogen by electrocatalytic ethylene glycol coupled with seawater electrolysis.

[0010] To achieve the above first object, the technical solution adopted by the present invention includes:

[0011] The present invention discloses an anode catalyst, comprising

[0012] Metal foam, as a substrate material;

[0013] MCo2O4 spinel oxide, supported on the metal foam; and

[0014] Palladium nanoparticles supported on the MCo2O4 spinel oxide;

[0015] Here, M represents metal Mn, Fe, Ni, Cu or Zn.

[0016] Furthermore, the mass density of the palladium nanoparticles is 1-5 mg / cm 2 , preferably 2 mg / cm 2 .

[0017] Furthermore, the foam metal is selected from commonly used foam metal substrates in the art, including but not limited to one or more of foam iron, foam cobalt, foam nickel and foam copper. Its shape can be adjusted according to application needs, and its thickness is preferably controlled at 0.5-2mm, preferably 1.6mm.

[0018] To achieve the above second purpose, the technical solution adopted by the present invention includes:

[0019] The present invention discloses a method for preparing the anode catalyst as described above, comprising the following steps:

[0020] A solution of cobalt salt, M metal salt, NH4F and urea is added to a high-pressure reactor, and the cleaned foamed metal is added, and a hydrothermal reaction is carried out at 100-140°C for 8-15 hours. After the reaction is completed, the obtained precursor is annealed to obtain a foamed metal loaded with MCo2O4 spinel oxide;

[0021] The foam metal loaded with MCo2O4 spinel oxide is immersed in a chloropalladic acid aqueous solution, kept at room temperature for 0.5-2 hours, and dried to obtain the product.

[0022] Furthermore, the molar ratio of the cobalt salt, the M metal salt, NH4F and urea is 1-2:0.5-1:1-3:3-6, preferably 2:1:3:6.

[0023] Further, the cobalt salt includes but is not limited to one or more of cobalt nitrate, cobalt acetate, cobalt chloride and cobalt sulfate; the M metal salt includes but is not limited to one or more of manganese nitrate, manganese chloride, manganese sulfate, ferric nitrate, ferric chloride, nickel nitrate, nickel chloride, nickel acetate, copper nitrate, copper chloride, copper sulfate, zinc nitrate, zinc chloride and zinc sulfate.

[0024] Furthermore, the chloropalladic acid aqueous solution needs to be adjusted to a pH value of 7-8 with a base in advance, preferably pH=7.

[0025] Further, the concentration of the chloropalladic acid aqueous solution is 1-15mmol / L; illustratively, the concentration of the chloropalladic acid aqueous solution can be 1mmol / L, 2mmol / L, 3mmol / L, 4mmol / L, 5mmol / L, 6mmol / L, 7mmol / L, 8mmol / L, 9mmol / L, 10mmol / L, 11mmol / L, 12mmol / L, 13mmol / L, 14mmol / L, 15mmol / L and the like.

[0026] Furthermore, the foam metal needs to be processed in advance to ensure that its surface is clean and free of impurities. The operation steps may be:

[0027] The foamed metal was ultrasonically cleaned with acetone, ethanol and distilled water in sequence, and then ultrasonically treated in 1-3.0 mol / L hydrochloric acid for more than 30 min, and then ultrasonically cleaned in deionized water and ethanol in sequence for multiple times, and finally dried for use.

[0028] It is understood by those skilled in the art that when the foam metal is placed in the high-pressure reactor, it should be inserted into the polytetrafluoroethylene liner as obliquely as possible to ensure that the precursor can grow on both sides of the foam metal.

[0029] Furthermore, the annealing condition is to heat to 300-400° C. at 2-3° C. / min and maintain for 2-3 hours.

[0030] To achieve the third objective, the technical solution adopted by the present invention includes:

[0031] The present invention discloses an application of the anode catalyst as described above in the electrocatalytic production of glycolic acid from ethylene glycol.

[0032] To achieve the fourth objective, the technical solution adopted by the present invention includes:

[0033] The present invention discloses an electrocatalytic system comprising the anode catalyst as described above and can be used for electrocatalytic production of glycolic acid from ethylene glycol, wherein the electrocatalytic system comprises:

[0034] Anode catalyst, cathode catalyst, anolyte and catholyte as described above.

[0035] Further, the anolyte comprises 1-3 mol / L potassium hydroxide and / or sodium hydroxide, 1-3 mol / L ethylene glycol, and 0.5-1 mol / L chloride salt;

[0036] The cathode electrolyte includes 1-3 mol / L potassium hydroxide and / or sodium hydroxide, and 0.5-1 mol / L chloride salt. In a specific embodiment, the chloride salt is NaCl, which is used to simulate seawater conditions.

[0037] In the anolyte and cathode electrolyte, the oxidation of ethylene glycol to glycolic acid has a lower oxidation potential (0.065 V vs RHE) compared with the chlorine oxidation in simulated seawater (1.72 V vs RHE), and is therefore more easily oxidized during the electrocatalytic process. Therefore, the electrocatalytic system can achieve the electrocatalytic oxidation of ethylene glycol to generate a thermodynamically stable oxidation product, glycolic acid, and can also produce an equal amount of hydrogen at the cathode.

[0038] Furthermore, the cathode catalyst may be a foam metal loaded with a metal phosphide, and the metal phosphide may be CoP, NiP, Fe3P, CuP, etc. In a specific embodiment, the cathode catalyst may be prepared by a hydrothermal method, and the specific operation may refer to the following steps:

[0039] Add a solution of metal salt, NH4F and urea into a high-pressure reactor, add the cleaned foam metal, and perform hydrothermal reaction at 100-140°C for 8-15 hours. After the reaction is completed, take it out, wash it with deionized water and ethanol in turn for several times, and then dry it in a vacuum drying oven. Then put sodium hypophosphite and the obtained precursor into a porcelain boat, with the sodium hypophosphite placed at one end of the porcelain boat close to the upwind port and the precursor at the other end. Then, introduce argon gas, heat to 400-600°C at a heating rate of 2-3°C per minute, and maintain for 1-4 hours to obtain the product.

[0040] To achieve the fifth objective, the technical solution adopted by the present invention includes:

[0041] The present invention discloses a method for producing hydrogen by electrocatalytic ethylene glycol coupled with seawater electrolysis, comprising the following steps:

[0042] The electrocatalytic system as described above is assembled into an electrolytic cell, and then a voltage is applied to carry out an electrocatalytic reaction to obtain the product.

[0043] Further, the electrolytic cell is selected from a conventional three-electrode H-type electrolytic cell, a two-electrode H-type electrolytic cell or a two-electrode flow electrolytic cell, wherein the three-electrode H-type electrolytic cell comprises: 1) an anode chamber: containing an anode catalyst electrode (1cm×1cm) and a Hg / HgO reference electrode, 2) a cathode chamber: containing a Pt sheet electrode (1cm×1cm), 3) a proton exchange membrane (Nafion117); the applied voltage is 0.7-1.2V compared to the reversible hydrogen electrode. The two-electrode H-type electrolytic cell comprises: containing an anode catalyst electrode (3cm×3cm), containing a cathode catalyst electrode (3cm×3cm), a proton exchange membrane (Nafion 117); the applied cell voltage is 0.4-2.1V. The double-electrode flow electrolytic cell comprises: a nickel electrolytic cell with flow channels, an anode catalyst (3cm×3cm), a cathode catalyst (3cm×3cm), a proton exchange membrane (Nafion 117) and a flow pump; the applied voltage is 1.2-1.5V and the temperature is room temperature.

[0044] Beneficial effects of the present invention:

[0045] The present invention discloses an anode catalyst, an electrocatalytic system containing the anode catalyst, and a method for producing hydrogen by electrocatalytic ethylene glycol coupled to seawater electrolysis. The anode catalyst is used in the electrocatalytic ethylene glycol coupled to seawater electrolysis to produce hydrogen, and exhibits high selectivity, catalytic activity, and stability, which is specifically reflected in that: when the industrial-grade current density (600mA cm 2 ), the operating voltage is only 1.14V; when ethylene glycol is completely electrolyzed, the yield of glycolic acid is as high as 92.6%; the hydrogen recovery rate is 99%; at the same time, the anode catalyst can achieve more than 100 hours of stable electrolysis under seawater conditions, which is better than all current palladium-based ethylene glycol oxidation catalysts.

[0046] Compared with the existing full water splitting or direct seawater electrolysis to produce hydrogen, this technology has lower power consumption and carbon emissions in producing the same amount of hydrogen, and the anode product has high value, making it suitable for grid-scale promotion and industrialization in arid and coastal areas. BRIEF DESCRIPTION OF THE DRAWINGS

[0047] The specific implementation modes of the present invention are further described in detail below in conjunction with the accompanying drawings.

[0048] Figure 1 The XRD spectrum of the Pd-CuCo2O4 / NF anode catalyst prepared in Example 1 is shown.

[0049] Figure 2 SEM images of the Pd-CuCo2O4 / NF anode catalyst prepared in Example 1 at different magnifications are shown.

[0050] Figure 3 The TEM image of the Pd-CuCo2O4 / NF anode catalyst prepared in Example 1 is shown.

[0051] Figure 4 The LSV curves of ethylene glycol electrolysis coupled with seawater using different anode catalysts in Example 5 are shown.

[0052] Figure 5 The LSV curves of the anode catalyst prepared in Example 1 for electrolysis of seawater and electrolysis of ethylene glycol coupled seawater are shown.

[0053] Figure 6 The Faraday efficiency diagram of the anode catalyst prepared in Example 1 at different voltages is shown.

[0054] Figure 7 The curve showing the conversion rate of the anode catalyst prepared in Example 1 for electrolysis of ethylene glycol coupled with seawater and the Faraday efficiency.

[0055] Figure 8 The LSV curve comparison between the complete hydrolysis of seawater and EGOR in the two-electrode H-type electrolytic cell of Example 6 is shown.

[0056] Fig. 9 The corresponding power consumption of mixed simulated seawater electrolysis (1M NaOH+0.5M NaCl+1M ethylene glycol) and alkaline simulated seawater electrolysis (1M NaOH+0.5M NaCl) at different current densities in Example 6 is shown.

[0057] Fig.10 Shown is a physical picture and structural schematic diagram of a dual-electrode flow electrolytic cell.

[0058] Fig.11 The it curves of alkaline natural seawater electrolysis and alkaline simulated seawater of Example 7 are shown.

[0059] Fig.12 The OCP curve in Example 7 is shown.

[0060] Fig.13 The it curve of electrolysis in Example 7 is shown.

[0061] Fig.14 The adsorption stripping curve of the ethylene glycol molecule in Example 8 is shown.

[0062] Fig.15 The OH of Pd-CuCo2O4 / NF in Example 8 is shown. - Adsorption curve.

[0063] Fig.16 The corrosion electrochemistry of Pd and Pd-CuCo2O4 / NF in Example 8 is shown. DETAILED DESCRIPTION

[0064] In order to more clearly illustrate the present invention, the present invention is further described below in conjunction with preferred embodiments and drawings. It should be clear that the described embodiments are only part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0065] Example 1: Preparation of anode catalyst Pd-CuCo2O4 / NF

[0066] The nickel foam was cut into pieces of 1 cm×2 cm in size and ultrasonically cleaned with acetone, ethanol and distilled water respectively. After being cleaned in sequence, the nickel foam was immersed in a 1.0 mol / L hydrochloric acid solution for ultrasonic treatment for 30 min, then washed with deionized water for 3 times and dried for later use.

[0067] A solution containing 1mmol Co(NO3)2·6H2O, 0.5mmol Cu(NO3)2·6H2O, 3mmol NH4F and 6mmol urea was prepared, transferred to a high-pressure reactor, the cleaned nickel foam was placed therein, transferred to an oven, heated to 120°C and maintained for 12 hours. After the reaction was completed, it was cooled to room temperature, the high-pressure reactor was taken out, the precursor after the reaction was cleaned and blown dry for later use; then, the precursor was placed in a muffle furnace and annealed in air, heated to 300°C at 2°C per minute, and maintained for 2 hours. After the reaction was completed, a foam metal loaded with spinel oxide CuCo2O4 was obtained, which was washed and set aside.

[0068] The foam metal loaded with spinel oxide CuCo2O4 was placed in a 5 mmol / L chloropalladic acid aqueous solution (the pH value was adjusted to 7 with sodium hydroxide), and then kept at room temperature for 1 hour. The foam metal was quickly taken out and washed with deionized water for several times, and then rinsed with ethanol twice, and finally placed in a vacuum drying oven at 60°C for 6 hours. The final material was recorded as Pd-CuCo2O4 / NF, where the mass density of palladium is 2 mg / cm 2 about.

[0069] Figure 1XRD showed that the prepared material contained palladium crystal phase and CuCo2O4, indicating that Pd-CuCo2O4 / NF was successfully prepared.

[0070] Figure 2 The SEM image shows that CuCo2O4 nanorods grow vertically on nickel foam, and Pd nanoparticles are loaded on the CuCo2O4 nanorods.

[0071] Figure 3 The TEM image shows that the palladium nanoparticles are evenly distributed on the CuCo2O4 nanorods.

[0072] Example 2: Preparation of anode catalyst Pd-NiCo2O4 / NF

[0073] The nickel foam was cut into pieces of 1 cm×2 cm in size and ultrasonically cleaned with acetone, ethanol and distilled water respectively. After being cleaned in sequence, the nickel foam was immersed in a 1.0 mol / L hydrochloric acid solution for ultrasonic treatment for 30 min, then washed with deionized water for 3 times and dried for later use.

[0074] A solution containing 1mmol Co(NO3)2·6H2O, 0.5mmol Ni(NO3)2·6H2O, 3mmol NH4F and 6mmol urea was prepared, transferred to a high-pressure reactor, the cleaned nickel foam was placed therein, transferred to an oven, heated to 120°C and maintained for 12 hours. After the reaction was completed, it was cooled to room temperature, the high-pressure reactor was taken out, the precursor after the reaction was cleaned and blown dry for later use; then, the precursor was placed in a muffle furnace for annealing in air, heated to 300°C at 2°C per minute, and maintained for 2 hours. After the reaction was completed, a foam metal loaded with spinel oxide NiCo2O4 was obtained, which was washed and set aside.

[0075] The foam metal loaded with spinel oxide NiCo2O4 was placed in a 5 mmol / L chloropalladic acid aqueous solution (the pH value was adjusted to 7 with sodium hydroxide), and then kept at room temperature for 1 hour. The foam metal was quickly taken out and washed with deionized water for several times, and then rinsed with ethanol twice, and finally placed in a vacuum drying oven at 60°C for 6 hours. The final material was recorded as Pd-NiCo2O4 / NF, where the mass density of palladium is 2 mg / cm 2 about.

[0076] Example 3: Preparation of anode catalyst Pd-MnCo2O4 / NF

[0077] The nickel foam was cut into pieces of 1 cm×2 cm in size and ultrasonically cleaned with acetone, ethanol and distilled water respectively. After being cleaned in sequence, the nickel foam was immersed in a 1.0 mol / L hydrochloric acid solution for ultrasonic treatment for 30 min, then washed with deionized water for 3 times and dried for later use.

[0078] A solution containing 1mmol Co(NO3)2·6H2O, 0.5mmol MnCl2·4H2O, 3mmol NH4F, and 6mmol urea was prepared, transferred to a high-pressure reactor, and the cleaned nickel foam was placed therein, transferred to an oven, heated to 120°C, and maintained for 12 hours. After the reaction was completed, it was cooled to room temperature, the high-pressure reactor was taken out, and the precursor after the reaction was cleaned and blown dry for use; then, the precursor was placed in a muffle furnace and annealed in air, heated to 300°C at 2°C per minute, and maintained for 2 hours. After the reaction was completed, a foam metal loaded with spinel oxide MnCo2O4 was obtained, which was washed and set aside.

[0079] The foam metal loaded with spinel oxide MnCo2O4 was placed in a 5 mmol / L chloropalladic acid aqueous solution (the pH value was adjusted to 7 with sodium hydroxide), and then kept at room temperature for 1 hour. The foam metal was quickly taken out and washed with deionized water for several times, and then rinsed with ethanol twice, and finally placed in a vacuum drying oven at 60°C for 6 hours. The final material was recorded as Pd-MnCo2O4 / NF, where the mass density of palladium is 2 mg / cm 2 about.

[0080] Example 4: Preparation of anode catalyst Pd-FeCo2O4 / NF

[0081] The nickel foam was cut into pieces of 1 cm×2 cm in size and ultrasonically cleaned with acetone, ethanol and distilled water respectively. After being cleaned in sequence, the nickel foam was immersed in a 1.0 mol / L hydrochloric acid solution for ultrasonic treatment for 30 min, then washed with deionized water for 3 times and dried for later use.

[0082] A solution containing 1mmol Co(NO3)2·6H2O, 0.5mmol FeCl2·9H2O, 3mmol NH4F, and 6mmol urea was prepared, transferred to a high-pressure reactor, the cleaned nickel foam was placed therein, transferred to an oven, heated to 120°C, and maintained for 12 hours. After the reaction was completed, it was cooled to room temperature, the high-pressure reactor was taken out, the precursor after the reaction was cleaned and blown dry for use; then, the precursor was placed in a muffle furnace for annealing in air, heated to 300°C at 2°C per minute, and maintained for 2 hours. After the reaction was completed, a foam metal loaded with spinel oxide FeCo2O4 was obtained, which was washed and set aside.

[0083] The foam metal loaded with spinel oxide FeCo2O4 was placed in a 5 mmol / L chloropalladic acid aqueous solution (the pH was adjusted to 7 with sodium hydroxide), and then kept at room temperature for 1 hour. The foam metal was quickly taken out and washed with deionized water for several times, and then rinsed with ethanol twice, and finally placed in a vacuum drying oven at 60°C for 6 hours. The final material was recorded as Pd-FeCo2O4 / NF, where the mass density of palladium is 2 mg / cm 2 about.

[0084] Comparative Example 1: Preparation of anode catalyst Pd-Ni(OH)2 / NF

[0085] The nickel foam was cut into pieces of 1 cm×2 cm in size and ultrasonically cleaned with acetone, ethanol and distilled water respectively. After being cleaned in sequence, the nickel foam was immersed in a 1.0 mol / L hydrochloric acid solution for ultrasonic treatment for 30 min, then washed with deionized water for 3 times and dried for later use.

[0086] The cleaned NF was placed in a 5 mmol / L chloropalladic acid aqueous solution (the pH was adjusted to 7 with sodium hydroxide), then heated to 90°C and maintained for 1 hour. The foam metal was quickly taken out and washed several times with deionized water, then rinsed twice with ethanol, and finally placed in a vacuum drying oven at 60°C for 6 hours. The resulting material was recorded as Pd-Ni(OH)2 / NF, where the mass density of palladium is 2 mg / cm 2 about.

[0087] Example 5: Electrolysis of ethylene glycol to produce glycolic acid in a three-electrode H-type electrolytic cell coupled with seawater electrolysis to produce hydrogen

[0088] The three-electrode H-type electrolytic cell includes: Pd-MCo2O4 / NF prepared in Examples 1-4 and Pd-Ni(OH)2 / NF prepared in Comparative Example 1 as anodes, with an electrode working area of ​​1cm×1cm; Hg / HgO as reference electrode, with an electrode working area of ​​1cm×1cm; Pt sheet as cathode, with an electrode working area of ​​1cm×1cm; anolyte: 1mol / L sodium hydroxide + 1mol / L ethylene glycol + 0.5mol / L NaCl; catholyte: 1mol / L potassium hydroxide + 0.5mol / L NaCl. The anode chamber and cathode chamber are connected by a proton exchange membrane (Nafion 117) with a diameter of 2cm, and voltage is applied for electrochemical testing. The results are shown in Figure 4-Figure 7 .

[0089] from Figure 4 It can be seen that Pd-CuCo2O4 / NF has the best performance in coupling ethylene glycol with seawater in this series of catalysts, so Pd-CuCo2O4 / NF was selected as the catalyst for subsequent experiments and performance characterization. Figure 5 It can be seen that when the current density reaches 200mA / cm 2 At that time, the voltage required for electrolysis of ethylene glycol was only 0.80V, which was much lower than the 1.80V required for electrolysis of water. When the current density reached the industrial level of 500mA / cm 2 At this time, the voltage required for electrolysis of ethylene glycol is only 1.06V. 1 H NMR can quantitatively monitor the amount of products in the solution after electrolysis. Figure 6 The Faradaic efficiency of producing glycolic acid by electrolysis at different voltages is the highest at 0.9 V, which is 98%. Figure 7 is the conversion rate of glycolic acid and the Faraday efficiency during the electrolysis process. It can be seen that with the extension of the electrolysis time, that is, the increase in the number of electrolytic charges, the conversion rate of ethylene glycol is higher, and when the electrolysis of ethylene glycol is complete, the yield of glycolic acid is as high as 92.6%.

[0090] Example 6: Electrolysis of ethylene glycol to produce glycolic acid in a two-electrode H-type electrolytic cell coupled with seawater electrolysis to produce hydrogen

[0091] Preparation of cathode catalyst CoP / NF

[0092] The nickel foam with a thickness of 1.6 mm was ultrasonically treated in 1 mol / L hydrochloric acid for 30 min, then ultrasonically cleaned in deionized water and ethanol for several times, and finally dried with a hair dryer for use; the cleaned nickel foam was placed in an aqueous solution containing 1 mmol cobalt nitrate hydrate, 3 mmol NH4F and 6 mmol urea, and transferred to a polytetrafluoroethylene-lined reactor, kept at 120°C in an oven for 12 hours, and after cooling to room temperature, the nickel foam was taken out, washed with deionized water and ethanol for several times, and dried in a vacuum drying oven; then 800 mg of sodium hypophosphite was weighed and placed at one end of the porcelain boat, and the above-mentioned foam metal loaded with active substances was placed at the other end, and then the porcelain boat was transferred to the middle part of the quartz tube, and the sodium hypophosphite was placed in the upwind position, and then the argon valve was opened, and argon was continuously introduced in a small gas flow for protection, and finally heated to 500°C at a heating rate of 2°C per minute and kept for 2 hours. Then it was cooled to room temperature, taken out, washed with deionized water and dried, and finally CoP / NF was obtained.

[0093] The two-electrode H-type electrolytic cell includes: Pd-CuCo2O4 prepared in Example 1 is used as an anode, and the electrode working area is 3cm×3cm; CoP / NF is used as a cathode, and the electrode working area is 3cm×3cm; two electrodes are constructed, and the electrolyte is 1M NaOH+0.5M NaCl+1M ethylene glycol. Figure 8 The LSV curves of hydrogen production by alkaline simulated seawater electrolysis and mixed simulated seawater electrolysis are shown. It can be clearly seen that when the value reaches 100 mA cm -2When the current density is low, the cell voltages are 1.92V and 0.88V respectively, with a difference of 1.04V, which greatly reduces the power consumption when producing the same amount of hydrogen. Fig. 9 As shown, for every cubic meter of hydrogen produced, the power consumption required for electrolyzing mixed simulated seawater to produce hydrogen is about 2.3 kWh lower than that of alkaline seawater at different current densities.

[0094] Example 7: Electrolysis of ethylene glycol to produce glycolic acid in a dual-electrode flow electrolysis cell coupled with seawater electrolysis to produce hydrogen

[0095] The dual-electrode flow electrolytic cell includes: Pd-CuCo2O4 prepared in Example 1 as an anode, the electrode working area is 3cm×3cm, CoP / NF as a cathode, the electrode working area is 3cm×3cm, the preparation method of CoP / NF is the same as that of Example 6, the anolyte is 1mol / L sodium hydroxide + 0.5mol / L NaCl + 1mol / L ethylene glycol flowing into the anolyte electrolytic cell at a flow rate of 0.15mL / min; the cathode electrolyte is 1mol / L sodium hydroxide + 0.5mol / L NaCl flowing into the cathode electrolytic cell at a flow rate of 4mL / min. The anode electrolytic cell and the cathode electrolytic cell are connected through a 3.5cm×3.5cm proton exchange membrane (Nafion 117), the applied voltage is 1.4V, the temperature is 25°C, and the electrolysis device is as follows Fig.10 shown. Fig.11 It curve of electrolysis. It can be seen from the figure that the anode catalyst can achieve stable electrolysis for more than 100 hours and can still maintain an ultra-high current density of 1.6A under the harsh conditions of natural seawater, which is better than all the current palladium-based ethylene glycol oxidation catalysts. Then, the excellent chlorine corrosion resistance of Pd-CuCo2O4 catalyst in seawater was studied in depth. Fig.12 It shows that under open circuit potential (OCP), the potential of Pd-CuCo2O4 drops the most after adding ethylene glycol molecules to the solution, indicating the excellent adsorption of ethylene glycol molecules on Pd-CuCo2O4. Generally speaking, differential capacitance is directly related to the dielectric constant and inversely proportional to the thickness of the electric double layer (EDL), while the thickness of EDL is positively correlated with the radius of the adsorbent. When inorganic anions are adsorbed on the catalyst surface to form an internal tight layer structure, the thickness of EDL will decrease, resulting in an increase in differential capacitance. On the contrary, organic molecules will reduce the interface capacitance due to their small dielectric constant and large volume. Fig.13 It means that in sodium chloride solution, the specific adsorption of ethylene glycol molecules by Pd-CuCo2O4 causes a decrease in differential capacitance, indicating that the adsorption of ethylene glycol molecules on the catalyst surface exceeds the adsorption of chloride ions, making the catalyst highly resistant to corrosion in seawater, thus maintaining very high stability.

[0096] Example 8: Electrochemical test of ethylene glycol and OH- Adsorption and electrochemical corrosion of anodic catalysts

[0097] The adsorption amount of ethylene glycol molecules on Pd and Pd-CuCo2O4 was determined by electrochemical stripping. The operation steps are: applying a certain voltage to allow ethylene glycol molecules to adsorb on the catalyst, then oxidizing the ethylene glycol molecules adsorbed on the catalyst surface by LSV, and calculating the ethylene glycol adsorption amount from the obtained oxidation peak area. Fig.14 As shown in the figure, the amount of ethylene glycol on Pd is much smaller than that on Pd-CuCo2O4, which is attributed to the abundant active sites after the combination of Pd and CuCo2O4. Subsequently, deoxygenation OER tests were carried out in alkaline simulated seawater (1M NaOH+0.5M NaCl) and 0.5M NaCl electrolyte under nitrogen protection. Fig.15 It can be seen that there is no obvious OH in the 0.5M NaCl electrolyte. - In alkaline simulated seawater, an obvious OH adsorption peak - This is consistent with the above experimental results, which proves that Pd and CuCo2O4 combine to adsorb ethylene glycol and OH. - The synergistic effect of adsorption is the source of the excellent stability of the catalyst under seawater conditions. At the same time, the corrosion current and corrosion potential of Pd and Pd-CuCo2O4 were calculated by Tafel extrapolation method. The smaller the corrosion current, the greater the corrosion potential, indicating that the catalyst has better corrosion resistance. Fig.16 It shows that Pd-CuCo2O4 is better than Pd (27.5 μA cm -2 , 0.39Vvs RHE) has a smaller corrosion current of 22.4μAcm -2 , and a larger corrosion potential of 0.42V vs RHE, demonstrating its stronger corrosion resistance.

[0098] Obviously, the above embodiments of the present invention are merely examples for clearly illustrating the present invention, and are not limitations on the implementation methods of the present invention. For ordinary technicians in the relevant field, other different forms of changes or modifications can be made based on the above description. It is impossible to list all the implementation methods here. All obvious changes or modifications derived from the technical solution of the present invention are still within the protection scope of the present invention.

Claims

1. An anode catalyst, characterized in that: include Metal foam, as a substrate material; MCo2O4 spinel oxide, supported on the metal foam; and Palladium nanoparticles supported on the MCo2O4 spinel oxide; Wherein, M represents metal Mn, Fe, Ni, Cu or Zn.

2. The anode catalyst according to claim 1, characterized in that The mass density of the palladium nanoparticles is 1-5 mg / cm 2 , preferably 2 mg / cm 2 .

3. The method for preparing an anode catalyst according to claim 1 or 2, characterized in that: The steps include: A solution of cobalt salt, M metal salt, NH4F and urea is added to a high-pressure reactor, and the cleaned foamed metal is added, and a hydrothermal reaction is carried out at 100-140°C for 8-15 hours. After the reaction is completed, the obtained precursor is annealed to obtain a foamed metal loaded with MCo2O4 spinel oxide; The foam metal loaded with MCo2O4 spinel oxide is immersed in a chloropalladic acid aqueous solution, kept at room temperature for 0.5-2 hours, and dried to obtain the product.

4. The preparation method according to claim 3, characterized in that: The molar ratio of the cobalt salt, the M metal salt, NH4F and urea is 1-2:0.5-1:1-3:3-6.

5. The preparation method according to claim 3, characterized in that: The pH value of the chloropalladic acid aqueous solution is 7-8.

6. The preparation method according to claim 3, characterized in that: The concentration of the chloropalladic acid aqueous solution is 1-15 mmol / L.

7. Use of the anode catalyst as claimed in claim 1 or 2 in the electrocatalytic production of glycolic acid from ethylene glycol.

8. An electrocatalytic system for preparing glycolic acid from ethylene glycol, characterized in that: include The anode catalyst, cathode catalyst, anode electrolyte and cathode electrolyte as claimed in claim 1 or 2.

9. The electrocatalytic system according to claim 8, characterized in that: The anolyte comprises 1-3 mol / L potassium hydroxide and / or sodium hydroxide, 1-3 mol / L ethylene glycol, and 0.5-1 mol / L chloride salt; The cathode electrolyte includes 1-3 mol / L potassium hydroxide and / or sodium hydroxide and 0.5-1 mol / L chloride salt.

10. A method for producing hydrogen by electrocatalytic ethylene glycol coupled with seawater electrolysis, characterized in that: The steps include: The electrocatalytic system according to claim 8 or 9 is assembled into an electrolytic cell, and then a voltage is applied to carry out an electrocatalytic reaction to obtain the product.

Citation Information

Cited By

  • Device for preparing glycollic acid and coupling hydrogen by electrooxidation of ethylene glycol

    CN122382587A